Case study: causes related to the losses of raw material in a flexible packaging industry - Zambonin, Leonardo Henrique; Vanin, Adriana Biasi; Azzolini, José Carlos; Meneghini, Cristiano (Brazilian Journal of Production Engineering, 2023)
The flexible packaging segment has major importance as they have vast possibility of application as containment, protection, and communication of products with the consumer. As the cost of packaging is incorporated to the final value of the product offered to the customer, companies have sought to reduce losses in the process to offer products with competitive prices. The present research aimed to map and quantify the losses of raw material in the productive process of obtaining flexible packaging and based on the results, present improvement proposals. For this, it was evaluated the historic of losses of the company in a period of ten months in wasted mass values in the warehouse sectors, cast and mixing/extrusion, sequentially the losses were valued in real and the 5 whys tool was used to diagnose the main causes of losses. It ended with the financial viability analysis of implantation of the improvement proposal presented. The results showed that the company had a loss of approximately R 321.363,56 in the period studied and that the main cause (71,7%) was the perforation of bags by the fork-lift forks in the warehouse sector. The study showed that application of the improvement proposal is viable, and that the total investment of R 24.957 will return in three months and twenty days.